Penerapan Strategi Pembelajaran Role Reversal Question Untuk Meningkatkan Kemampuan Mengajukan Pertanyaan Siswa Kelas IV UPT SDN 017 Langgini Pada Mata Pelajaran IPAS - Adila, Nur (Science and Education Journal (SICEDU), 2025)
This research was motivated by the low ability to ask qestions of students in class IVA. This research aims to improve the ability to ask questions by appliying the Role Reversal Questions (RRQ) learning model to class IV students at UPT SDN 017 Langgini. This research is classroom action research (PTK), which was carried out in two cycles and each cycle consistend of two meetings. The subjects in this research were all 20 class IVA students. Data collection techniques include observation and documentations techniques. Meanwhile, the data analysis include analysis tecniques used are a  combination of qualitative data and quantitative data. Based on the results of research that has been carried out in 2 cycles, in the first meeting of cycle I, Student sw ho were skilled at asking questions, there were 5 students with a percentage of 25%. At meeting 2,this rose to 8 studentswith a percentage of 40%. Meanwhile, in cycle ll, meeting 1, there were students who were skilled at asking questions. 10 students with a percentage of 50% and at meeting 2 there was an increase to 12 students with a percentage of 60%. Based on the results of this research, it shows that by implementing the Role Reversal Questions (RRQ) learning model it can improve the ability to ask questions of class IV students at UPT SDN 017 Langgini.